The Role of Business Center Alfamart in Improving Student Marketing Competencies - Selviani Putri Anggia; Wening Patmi Rahayu; Didik Indratno; Puji Rahayu; Siti Mutmainah (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2017)
The purpose of this study is to know an overall research, optimization and the role of business center SMKN 1 Turen. The research type is qualitative descriptive. The procedure of Data collection used observation, interview, and documentation. The results show that the design is similar with Alfamart store, the school optimizes it as a real practice place not only the simulation, the infrastructure facilities are complete and promotes in improving psychomotor competence that is Alfaclass students can do arrangement product using FIFO method, operate the cash register, and serving consumer by friendly